Laser interstitial thermal therapy in pediatric neurosurgery: a prospective nationwide study on indications, safety, and early outcomes - Silas Haahr Nielsen; Jon Foss-Skiftesvik; Torstein Ragnar Meling; Astrid Marie Sehested; Christina Engel Høi-Hansen; Michael Thude Callesen; Gorm von Oettingen; Adam Espe Hansen; Jane Skjøth-Rasmussen; Rune Rasmussen (Child's Nervous System, 2026)
Abstract Purpose To evaluate indications, safety, and early outcomes of MRI-guided laser interstitial thermal therapy (LITT) in a nationwide prospective pediatric cohort and to assess the feasibility of same-session stereotactic biopsy. Methods All consecutive pediatric patients (≤ 18 years) who underwent LITT at the Danish National Referral Center between June 2021 and October 2025 were prospectively enrolled. Demographic, clinical, radiological, and surgical variables were recorded. Safety outcomes included complications, neurological deficits, length of stay, and 30-day readmission. Seizure outcomes were assessed by Engel classification and tumor response on follow-up MRI. Results A total of 27 children (mean age 11.6 ± 4.3 years) underwent LITT, including 18 treated for drug-resistant epilepsy and 9 for tumor indications. Same-session stereotactic biopsy was performed in 10 patients without biopsy-related complications or interference with ablation. Transient neurological deficits were observed in 5 patients and persistent deficits in 3. Hospital stay was 1–2 days in 23 patients, and no 30-day readmissions occurred. Seizure freedom (Engel class I) was achieved in 67% and 50% at 12 and 24 months, respectively. In tumor patients, clinical and MRI follow-up were available in all 9 patients, with one radiographic recurrence during follow-up. Conclusion In this nationwide prospective cohort of 27 consecutively treated children, LITT demonstrated a favorable safety profile across epilepsy and tumor indications. Same-session stereotactic biopsy was feasible and safe, supporting LITT as a minimally invasive option in carefully selected pediatric patients.